Influence of fuel-to-oxidizer ratio, potential of hydrogen and annealing temperature on the structural and optical properties of nanocrystalline MgO powders synthesized by the hydrothermal method - Bruska Azhdar (Journal of Experimental Nanoscience)
Nanocrystalline magnesium oxide powders (MgO) were prepared using a hydrothermal method. In various fuel-to-oxidizer ratios (F/O) and precursor solutions with pH levels from 8 to 12, magnesium nitrate hexahydrate Mg(NO3)2 was utilized as an oxidizer and polyvinyl alcohol (PVA) as a fuel. To improve crystallinity and phase purity, these materials were annealed for two hours at varied temperatures. XRD, FTIR, EDS, FESEM and DRS were used to study the MgO nanopowders’ structure, vibration, elemental and optical properties. The fuel-to-oxidizer ratios, annealing temperatures and pH values greatly affected the samples’ properties. The synthesized powders had a particle size distribution in the range of 18–49 nm. The XRD results showed that the crystallite percent of the MgO phase grew with an increase in the F/O from 0.5 to 0.75, and then, it decreased at F/O = 1. The maximum percent of crystallites was observed at pH = 8. By increasing the annealing temperatures, the crystallite size of the samples increased from 22.82 nm to 49.06 nm, while the specific surface area and dislocation density decreased from 20.59 m2/g to 7.83 m2/g and 0.0006 nm−2 to 0.0001 nm−2, respectively. FTIR spectra results indicated that the MgO band peaking at (418–688 cm−1) was high at pH value 8, then it reduced at pH 10 and finally, this peak had the smallest size at pH = 12. Further confirmation of MgO presence and its homogeneity in the final product was approved through EDS measurements. DRS spectra were used to obtain energy gap using Kubelka–Munk relation and noticed in the range of 5.72–5.89 eV for MgO NPs.